Play on : the new science of elite performance at any age - Bercovici, Jeff (Houghton Mifflin Harcourt, 2018)
"A lively, thoroughly researched tour of the latest in fitness science and technology, and the strategies of elite and amateur athletes who are performing at peak levels for decades longer than before"--